Impact of 18F-Fluorodeoxyglucose positron emission tomography on management of cancer of unknown primary: systematic review and meta-analysis. (December 2021) - Woo, Sungmin; Becker, Anton S.; Do, Richard K.G.; Schöder, Heiko; Hricak, Hedvig; Alberto Vargas, H.
Abstract: Background: Cancers of unknown primary (CUP) have traditionally been treated empirically, with a dismal prognosis. Compared with standard diagnostic tests, including CT and MRI, imaging with 18 F-fluorodeoxyglucose (FDG) PET or PET/CT has shown the capacity to better identify the primary tumour site and detect additional sites of metastasis. However, its clinical impact is not well established. We performed a systematic review and meta-analysis of prior studies to assess the impact of FDG-PET or PET/CT on the management of patients with CUP. Materials and methods: Pubmed and EMBASE databases were searched up to 4th February 2021. Studies that reported the proportion of patients with CUP who experienced a management change after FDG-PET or PET/ computed tomography (CT) were included and the proportions were pooled using the random-effects model. Study quality was assessed using QUADAS-2. Subgroup analysis was conducted to explore heterogeneity. Results: Thirty-eight studies (involving 2795 patients) were included. The pooled proportion of patients with management changes was 35% (95% confidence interval 31%–40%). There was substantial heterogeneity among the studies (Q-test, p < 0.01; I 2  = 82%). The specific reason for management change was more commonly detection of the primary site (22% [95% CI 18–28%]) than detection of additional metastatic sites (14% [95% CI 10–19%]). The pooled proportions of patients with management changes were similar among numerous subgroups (range, 32.8%–38.2%). Conclusion: FDG-PET or PET/CT had a meaningful impact on the management of patients with CUP. Approximately, a third of patients had their management changed because of FDG-PET or PET/CT results, and this finding was consistent across numerous subgroups. Highlights: In 38 studies with cancer of unknown primary, 18F-fluoro-2-deoxyglucose positron emission tomography changed management 35%.c. These were related to find the primary site (22%) or additional metastatic sites (14%). Similar pooled proportions were seen across subgroups (32.8–38.2%).